2006
DOI: 10.1177/009286150604000107
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Drug Information Resources in Alabama Pharmacy Facilities

Abstract: Drug'mterocliontexts 204 33.8 R f w n t w n e t 1 02 16.9 uspa# 97 16.1 AHB § 73 121 M i i d X 54 8.9 14 2.3 bels indicated that Alabama had 1,197 retail/ community and 159 hospitaVmenta1 health pharmacies. Based on this estimate, the total survey return rates for these facilities were 34% and 46%, respectively. AVAILABLE RESOURCES BY ALL PHARMACIES Enumeration of available D1 resources for Alabama pharmacies was one of the major objectives for this study: Table 1 depicts the survey results of the resources in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…"Adverse drug reactions and side effects" was the option most frequently chosen, followed by "dosing", then "compatibility and stability" (Table 3). In a recent publication, Schrimsher et al found that drug interactions, adverse reactions, and over-the-counter (OTC) questions were at the top of the list 42. Here men and women showed identical patterns, but differences were observed by age group.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…"Adverse drug reactions and side effects" was the option most frequently chosen, followed by "dosing", then "compatibility and stability" (Table 3). In a recent publication, Schrimsher et al found that drug interactions, adverse reactions, and over-the-counter (OTC) questions were at the top of the list 42. Here men and women showed identical patterns, but differences were observed by age group.…”
Section: Resultsmentioning
confidence: 97%
“…Drug Facts and Comparisons (Facts & Comparisons), a print resource, was the second most frequently used reference. Two previous similar studies found that Facts & Comparisons was the reference most available to pharmacists 25,42. The Physician's Desk Reference, until recently a popular source of drug use information, was not selected by a single respondent.…”
Section: Resultsmentioning
confidence: 99%
“…A recent survey of 604 Alabama pharmacies demonstrated that over 90% of respondents reported availability of Drug Facts and Comparisons in the facility. 11 Although Alabama law suggests that pharmacies have the latest edition of Drug Facts and Comparisons, any reference or electronic media meeting the level of pharmacy practiced at the site will satisfy state laws for reference availability. 12 Surveys administered to community pharmacies in other states similarly have indicated that Drug Facts and Comparisons is the most frequently utilized resource.…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, reference texts are still trusted by pharmacists (Wong, Ko, & Sklar, 2009). Even in the United States, a survey performed among Alabama pharmacy facilities indicated a high use of textbooks as medicine information resources such as Drug Facts and Comparisons and Physician's Desk Reference (Schrimsher, Freeman, & Kendrach, 2006). Clauson, Fass, and Seamon (2008a) explored the legal requirements for maintaining medicines information resources in pharmacies across the 50 states in the United States and found that two states, Minnesota and South Dakota (3.8% of states), required print references.…”
Section: Textbooks Books and Handbooksmentioning
confidence: 99%